Thermal and numerical simulation of mould electromagnetic stirring of GCr15 bearing steel. Issue 18 (12th December 2019) - Jiang, Danqing; Wang, Rui; Zhu, Longqiang; Zhang, Qiong; Li, Chuanjun; Wang, Jiang; Ren, Zhongming
ABSTRACT: The thermal and numerical simulation of the mould electromagnetic stirring (M-EMS) during continuous casting (CC) of the GCr15 bearing steel was performed. The thermal simulation apparatus with the M-EMS was used to examine the effect of stirring parameters on solidification structures. It was found that M-EMS enlarged the equiaxed grain regions, refined the grain size and resulted in more homogeneous distribution of the solute elements. The flow field in the mould was simulated to show the M-EMS intensity, which is in accordance with experimental observations. The mechanical properties of the blooms obtained at the current of 300A and frequency of 5 Hz are optimal.